P048 MRI T2 relaxometry-based measures of intestinal inflammation in a human intestinal permeability model: a pilot study. (16th January 2018) - Scott, R; Hoad, C; Williams, H; Ortori, C; Grove, J; Moran, G; Gowland, P; Aithal, G
Abstract: Background: Contrast-based Magnetic resonance (MR) enterography has a diagnostic accuracy of up to 90% 1 to detect ulcer healing in Crohn's disease (CD). Intravenous gadolinium T1 -based imaging carries a risk of nephrogenic systemic fibrosis and allergic reaction. FDA safety alerts have been issued regarding its use in humans. Moreover, T2 -based measures are still presently subjective. Increased small bowel (SB) permeability has been described in CD. 2 The best validated gold standard measure of SB permeability is the Lactulose/Mannitol (LMR) urinary excretion test. A change in intestinal permeability may be induced with an oral indomethacin challenge. 3 We aimed to develop non-invasive contrast-free T2 relaxometry MRI measure of intestinal inflammation using intestinal permeability as a surrogate of intestinal injury. Methods: Healthy participants ( n = 24) were enrolled on a 2 × 2 double-blind provocation study consisting of placebo and indomethacin (75 mg dose taken 16 h and 4 h prior to the scan) to induce increased permeability with >2 weeks washout time between arms. 3 Newly developed quantitative MR measures of SB wall thickness, T2 relaxometry, and motility [4] were compared with a 2 h lactulose/mannitol urinary excretion ratio (LMR). Coronal MR scans were performed on 3 Tesla Philips MRI scanner (Best, the Netherlands) in prone position. Two doses of 20 mg intravenous Buscopan were administered to reduce peristalsis. Ethical permission was granted by the University of Nottingham. Data are presented as median and Interquartile range (IQR). Non-parametric analyses were undertaken. Results: Data from 22 participants (14 females; 23 years (IQR 22–25), BMI of 23.7 (IQR 21.8–27.8) kg/m 2 ) were available for a per-protocol analyses. Indomethacin induced significant changes from placebo in LMR from 0.019 (IQR 0.016–0.026) to 0.025 (IQR 0.021–0.039) ( p = 0.002) and T2 SB decay from 0.09 s to 0.13 s ( p = 0.009). SB wall thickness of 2.56 mm (2.41–2.72) showed no significant change with the challenge. Global SB motility showed a decreasing trend with the indomethacin challenge (0.300 (0.251–0.353) to 0.272 (0.253–0.305). Conclusions: Newly developed non-contrast MRI techniques can sensitively measure in vivo SB wall thickness, T2 relaxometry and motility in healthy volunteers. MR measures of SB wall T2 are significantly increased with increased permeability associated with indomethacin provocation. Further validation to analyse the intra-class correlation is underway. Dowstream analyses will correlate these outcomes to standard endoscopy and MR measures of disease activity in CD. References: 1. Ordas I, Rimola J, Rodriguez S, et al. Accuracy of magnetic resonance enterography in assessing response to therapy and mucosal healing in patients with Crohn's disease. Gastroenterology, 2014:374–82. 2. Hollander D, Vadheim CM, Brettholz E, et al. Increased intestinal permeability in patients with Crohn's disease and their relatives. A possible etiologic factor. Ann Intern Med, 1986;105:883–5. 3. Vanuytsel T, van Wanrooy S, Vanheel H, et al . Psychological stress and corticotropin-releasing hormone increase intestinal permeability in humans by a mast cell-dependent mechanism. Gut, 2013;63:1–7. 4. Menys A, Taylor SA, Emmanuel A, et al. Global small bowel motility: Assessment with dynamic MR imaging. Radiology, 2013;269:443–50.